Does playing a sports active video game improve young children's ball skill competence? - Johnson, T. M.; Ridgers, N. D.; Hulteen, R. M.; Mellecker, R. R.; Barnett, L. M. (Journal of Science and Medicine in Sport, 2016)
Objectives: Actual and perceived object control (commonly ball) skill proficiency is associated with higher physical activity in children and adolescents. Active video games (AVGs) encourage whole body movement to control/play the electronic gaming system and therefore provide an opportunity for screen time to become more active. The purpose of this study was to determine whether playing sports AVGs has a positive influence on young children's actual and perceived object control skills. Design: Two group pre/post experimental design study. Methods: Thirty-six children aged 6-10 years old from one school were randomly allocated to a control or intervention condition. The Test of Gross Motor Development-3 assessed object control skill. The Pictorial Scale of Perceived Competence for Young Children assessed perceived object control skill. The intervention consisted of 6 × 50 min lunchtime AVG sessions on the Xbox Kinect. Two to three sport games were chosen for participants to play each session. General linear models with either perceived object control or actual object control skill as the outcome variables were conducted. Each base model adjusted for intervention status and pre-score of the respective outcome variable. Additional models adjusted for potential confounding variables (sex of child and game at home). Results: No significant differences between the control and intervention groups were observed for both outcomes. Conclusions: This study found that playing the Xbox Kinect does not significantly influence children's perceived or actual object control skills, suggesting that the utility of the Xbox Kinect for developing perceived and actual object control skill competence is questionable.